Increased Nitrosoglutathione Reductase Activity in Hypoxic Pulmonary Hypertension in Mice - Xiling Wu; Lizhong Du; Xuefeng Xu; Linhua Tan; Ruyi Li (Elsevier, 2010)
Altered S-nitrosothiols (RSNO) signaling is linked to pulmonary hypertension. Recent studies have shown that S-nitrosoglutathione (GSNO) reductase (GSNOR) catalyzes the degradation of GSNO and indirectly regulates the level of RSNO in vivo. Our present study tested the hypothesis that chronic hypoxia causes pulmonary hypertension, in part, by the change of GSNOR activity that contributes to the depletion of RSNO. Male mice were exposed to normobaric hypoxia in a ventilated chamber for 1 to 21 days or normoxia for 21 days. Right ventricular systolic pressure, right ventricle hypertrophy, and the number and media thickness of muscular pulmonary vessels increased significantly after 21 days of hypoxic exposure. Hypoxia induced the overexpression of endothelial nitric oxide synthase and inducible nitric oxide synthase. The mRNA expression of GSNOR decreased on day 1 of hypoxic exposure, but increased significantly on day 7 compared with the normoxic group. The protein expression of GSNOR increased significantly in the lung tissue after 7 days of hypoxic exposure and its enzymatic activities also increased. Both the ratios of glutathione to glutathione disulfide and nitrate to nitrite were significantly lower in the hypoxic groups than in the normoxic controls. The results suggest an increased GSNOR activity interfered with the metabolism of RSNO in mice with hypoxic pulmonary hypertension. An imbalanced of redox status is associated with the pathogenesis of hypoxic pulmonary hypertension. Keywords:: hypoxia, S-nitrosoglutathione reductase, endothelial nitric oxide synthase, glutathione and glutathione disulfide